( 2 0 0 0 × 2 0 0 8 × 2 0 0 9 × 2 0 1 7 ) + 1 2 9 6 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Ya please send a solution to know how to do it ......................
I have posted a solution.
Ashwin- write a solution to this problem, so I know you solved it legit
Can you write out the solution yourself? It would certainly benefit the community!
We have: ( 2 0 0 0 × 2 0 0 8 × 2 0 0 9 × 2 0 1 7 ) + 1 2 9 6 = ?
Set 2000 as x: ( x × ( x + 8 ) × ( x + 9 ) × ( x + 1 7 ) ) + 1 2 9 6 = ?
Now:
( ( ( x + 8 ) × ( x + 9 ) ) × ( ( x + 1 7 ) × ( x ) ) ) + 1 2 9 6 = ?
= ( x 2 + 1 7 x + 7 2 ) × ( x 2 + 1 7 x ) + 1 2 9 6 = ?
= ( x 2 + 1 7 x + 3 6 + 3 6 ) × ( x 2 + 1 7 x + 3 6 − 3 6 ) + 1 2 9 6 = ?
Now we can set ( x 2 + 1 7 x + 3 6 ) as A and 3 6 as B.
( ( A + B ) ( A − B ) = A 2 − B 2 )
= ( x 2 + 1 7 x + 3 6 ) 2 − 3 6 2 + 3 6 2 )
= ( x 2 + 1 7 x + 3 6 ) 2
Plugging 2000 for x gives us 4034036.
Log in to reply
In step 2, your order of operations is wrong
I did solve it legit.
Problem Loading...
Note Loading...
Set Loading...
I replaced 2000 with x . This makes 2 0 0 0 × 2 0 0 8 × 2 0 0 9 × 2 0 0 9 = x × ( x + 8 ) × ( x + 9 ) × ( x + 1 7 ) .
I simplified it as ( x 2 + 1 7 x ) × ( x 2 + 1 7 x + 7 2 )
further replacing x 2 + 1 7 x with y , I get y × ( y + 7 2 )
putting it back in the original problem, we get y 2 + 7 2 y + 1 2 9 6
Solving we get the answer y + 3 6
since y = x 2 + 1 7 x , we get x 2 + 1 7 x + 3 6
since x = 2 0 0 0 , we get the answer as 4034036